2013
DOI: 10.3889/mjms.1857-5773.2013.0320
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Depth of Embryo Replacement into the Uterine Cavity under Transabdominal Ultrasound Guidance on In Vitro Fertilization and Embryo Transfer Outcome

Abstract: The aim of the present study was to determine the importance of the depth of embryo replacement into the uterine cavity (upper or lower half endometrial cavity) on the implantation clinical pregnancy rates. Material and Methods:In this prospective observational were included 160 patients underwent controlled ovarian hyperstimulation followed by IVF/ICSI and embryo transfer. On the day of embryo transfer under direct transabdominal ultrasound guidance, the transfer catheter was advanced to a defined distance fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Although the final position of the air bubble in the endometrium cannot be predicted in advance, it can be used to predict the treatment outcomes. 8 A few studies have focused on the transfer depth, reporting that different transfer depths can affect treatment outcomes and optimal transfer depth can significantly increase success rates 8,16 ; however, the studies reached different conclusions and did not report the endometrial thickness at the transfer position. Consistent with those previous studies, a transfer depth between 10 and 20 mm led to a higher rate of implantation, pregnancy, and live delivery, and a lower frequency of spontaneous abortion, as compared with a depth of more than 20 mm in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the final position of the air bubble in the endometrium cannot be predicted in advance, it can be used to predict the treatment outcomes. 8 A few studies have focused on the transfer depth, reporting that different transfer depths can affect treatment outcomes and optimal transfer depth can significantly increase success rates 8,16 ; however, the studies reached different conclusions and did not report the endometrial thickness at the transfer position. Consistent with those previous studies, a transfer depth between 10 and 20 mm led to a higher rate of implantation, pregnancy, and live delivery, and a lower frequency of spontaneous abortion, as compared with a depth of more than 20 mm in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The first investigated the relationship between air bubble position and pregnancy rates in 315 blastocyst transfers, but differently from our study, the EFD was measured with trans-abdominal US [11]. The PR was found to be significantly lower when the EFD was longer than 10mm [11]. The second study included 409 ETs and failed to demonstrate any significant difference in PR and IR that could be related to the site of embryo release [12].…”
Section: Global Journal Of Reproductive Medicinementioning
confidence: 73%
“…A couple of studies using US detection of air bubble localization have been reported to date, but differently from ours they are both retrospective and include much less observations [11,12]. The first investigated the relationship between air bubble position and pregnancy rates in 315 blastocyst transfers, but differently from our study, the EFD was measured with trans-abdominal US [11].…”
Section: Global Journal Of Reproductive Medicinementioning
confidence: 89%
See 2 more Smart Citations